Adipose depot gene expression and intelectin‐1 in the metabolic response to cancer and cachexia. Issue 4 (31st March 2020) - Miller, Janice; Dreczkowski, Gillian; Ramage, Michael I.; Wigmore, Stephen J.; Gallagher, Iain J.; Skipworth, Richard J.E.
Abstract: Background: Cancer cachexia is a poorly understood metabolic consequence of cancer. During cachexia, different adipose depots demonstrate differential wasting rates. Animal models suggest adipose tissue may be a key driver of muscle wasting through fat–muscle crosstalk, but human studies in this area are lacking. We performed global gene expression profiling of visceral (VAT) and subcutaneous (SAT) adipose from weight stable and cachectic cancer patients and healthy controls. Methods: Cachexia was defined as >2% weight loss plus low computed tomography‐muscularity. Biopsies of SAT and VAT were taken from patients undergoing resection for oesophago‐gastric cancer, and healthy controls ( n = 16 and 8 respectively). RNA was isolated and reverse transcribed. cDNA was hybridised to the Affymetrix Clariom S microarray and data analysed using R/Bioconductor. Differential expression of genes was assessed using empirical Bayes and moderated‐ t ‐statistic approaches. Category enrichment analysis was used with a tissue‐specific background to examine the biological context of differentially expressed genes. Selected differentially regulated genes were validated by qPCR. Enzyme‐linked immunosorbent assay (ELISA) for intelectin‐1 was performed on all VAT samples. The previously‐described cohort plus 12 additional patients from each group also had plasma I = intelectin‐1 ELISA carried out. Results: In VAT vs. SAT comparisons, there were 2101, 1722, and 1659 significantly regulated genes in the cachectic, weight stable, and control groups, respectively. There were 2200 significantly regulated genes from VAT in cachectic patients compared with controls. Genes involving inflammation were enriched in cancer and control VAT vs. SAT, although different genes contributed to enrichment in each group. Energy metabolism, fat browning (e.g. uncoupling protein 1), and adipogenesis genes were down‐regulated in cancer VAT (P = 0.043, P = 5.4 × 10 −6 and P = 1 × 10 −6 respectively). The gene showing the largest difference in expression was ITLN1, the gene that encodes for intelectin‐1 (false discovery rate‐corrected P = 0.0001), a novel adipocytokine associated with weight loss in other contexts. Conclusions: SAT and VAT have unique gene expression signatures in cancer and cachexia. VAT is metabolically active in cancer, and intelectin‐1 may be a target for therapeutic manipulation. VAT may play a fundamental role in cachexia, but the down‐regulation of energy metabolism genes implies a limited role for fat browning in cachectic patients, in contrast to pre‐clinical models.